2022
DOI: 10.1038/s41467-022-31812-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of immunity-related GTPase GM4951 leads to nonalcoholic fatty liver disease without obesity

Abstract: Obesity and diabetes are well known risk factors for nonalcoholic fatty liver disease (NAFLD), but the genetic factors contributing to the development of NAFLD remain poorly understood. Here we describe two semi-dominant allelic missense mutations (Oily and Carboniferous) of Predicted gene 4951 (Gm4951) identified from a forward genetic screen in mice. GM4951 deficient mice developed NAFLD on high fat diet (HFD) with no changes in body weight or glucose metabolism. Moreover, HFD caused a reduction in the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Mouse primary hepatocytes were isolated following a 2-step collagenase digestion protocol (20). Briefly, mice were anesthetized and the liver was perfused in situ with 50 ml Hank's Balanced Salt Solution (HBSS) through the portal vein, followed by 8 mL of liver digestion media containing 2M HEPES, 1% Penicillin-Streptomycin (P/S) Solution, and 0.08% type 4 collagenase.…”
Section: Primary Hepatocyte Isolationmentioning
confidence: 99%
“…Mouse primary hepatocytes were isolated following a 2-step collagenase digestion protocol (20). Briefly, mice were anesthetized and the liver was perfused in situ with 50 ml Hank's Balanced Salt Solution (HBSS) through the portal vein, followed by 8 mL of liver digestion media containing 2M HEPES, 1% Penicillin-Streptomycin (P/S) Solution, and 0.08% type 4 collagenase.…”
Section: Primary Hepatocyte Isolationmentioning
confidence: 99%
“…In terms of genetic factors, GM4951, an immunity-related GTPase, can regulate liver lipid metabolism. Experiments show that a deficiency in GM4951 can lead to “lean” NAFLD [ 37 ]. Our results showed that TG only mediated about 2.98% of the positive correlation between BMI and non-obese NAFLD, indicating the involvement of other mechanisms mediating BMI and non-obese NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…And latest research revealed that LVMI increased progressively and LV diastolic function worsened with increasing number of steatosis scores in NAFLD patients. It also showed that liver steatosis, as identified by use of biochemical scores, predicted LV hypertrophy and diastolic dysfunction independently of blood pressure and obesity, and this association was independent of the HOMA-index for LV diastolic dysfunction [ 43 ]. Then there was a research showing that metabolic dysfunction-associated fatty liver disease patients had increased interventricular septum thickness, left ventricular posterior wall thickness, LVM and LVMI, and more patients with MAFLD had LV diastolic dysfunction compared to the normal group (60.8% vs 24.6%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%